Agricultural Bio-Stimulant Application to Enhance Phosphorus Availability in Grain Sorghum - A. Obour (Kansas Agricultural Experiment Station Research Reports, 2017)
This study was conducted to determine the effectiveness of AgZyme and SuperHume (both products of Ag Concepts Corp) application on phosphorus (P) uptake and utilization efficiency in grain sorghum. Treatments were a control, 30 lb P2O5/a, 20 oz/a AgZyme, 20 oz/a AgZyme + 30 lb P2O5/a, 20 oz/a AgZyme + 30 lb P2O5/a + 6 qt/a SuperHume, which were arranged in a randomized complete block design with four replications. Preliminary results in 2016 showed grain sorghum aboveground biomass, grain moisture content, and test weight were not affected by the application of either P alone or with a bio-stimulant. Applying AgZyme alone resulted in a 9 bu/a yield increase above the control. The application of AgZyme with P did not improve grain yield compared to control. This observation was possibly due to greater initial soil P content (45 lb P/a) at the study site. However, tissue P concentration was greatest when Ag- Zyme was applied with 30 lb P2O5/a. Applying AgZyme, SuperHume, and 30 lb P2O5/a together reduced both sorghum grain yield and tissue P concentration.
Keywords: Bio-stimulant; Humic Acid; AgZyme; SuperHume; grain sorghum